Impact of Office Facilities and Workplace Milieu on Employees' Performance: A Case Study of Sargodha University - Parveen, Sajida; Sohail, Malik Muhammad; Naeem, Farheen; Azhar, Zarqa; Khan, Saddat Hasnain (Asian Journal of Empirical Research, 2012)
It was important to maintain a comfortable, safe, supportive physical environment to help workers stay motivated and productive. This study aims to explore the impact of office facilities and workplace milieu on employees’ performance in a university of Sargodha. A sample of 150 respondents of male and female employees of both teaching and non-teaching category was selected. Chi-square and Gamma test were applied to interpret the findings of study.